Testing of SNS-032 in a panel of human neuroblastoma cell lines with acquired resistance to a broad range of drugs - Löschmann, Nadine; Michaelis, Martin; Rothweiler, Florian; Zehner, Richard; Cinatl, Jaroslav; Voges, Yvonne; Sharifi, Mohsen; Riecken, Kristoffer; Meyer, Jochen; Deimling, Andreas von; Fichtner, Iduna; Ghafourian, Taravat; et al. (Translational oncology, 2013)
Novel treatment options are needed for the successful therapy of patients with high-risk neuroblastoma. Here, we investigated the cyclin-dependent kinase (CDK) inhibitor SNS-032 in a panel of 109 neuroblastoma cell lines consisting of 19 parental cell lines and 90 sublines with acquired resistance to 14 different anticancer drugs. Seventy-three percent of the investigated neuroblastoma cell lines and all four investigated primary tumor samples displayed concentrations that reduce cell viability by 50% in the range of the therapeutic plasma levels reported for SNS-032 (<754 nM). Sixty-two percent of the cell lines and two of the primary samples displayed concentrations that reduce cell viability by 90% in this concentration range. SNS-032 also impaired the growth of the multidrug-resistant cisplatin-adapted UKF-NB-3 subline UKF-NB-3rCDDP1000 in mice. ABCB1 expression (but not ABCG2 expression) conferred resistance to SNS-032. The antineuroblastoma effects of SNS-032 did not depend on functional p53. The antineuroblastoma mechanism of SNS-032 included CDK7 and CDK9 inhibition-mediated suppression of RNA synthesis and subsequent depletion of antiapoptotic proteins with a fast turnover rate including X-linked inhibitor of apoptosis (XIAP), myeloid cell leukemia sequence 1 (Mcl-1), baculoviral IAP repeat containing 2 (BIRC2; cIAP-1), and survivin. In conclusion, CDK7 and CDK9 represent promising drug targets and SNS-032 represents a potential treatment option for neuroblastoma including therapy-refractory cases.
Available online 19 February 2014
Gesehen am 21.05.2021